Abstracts of Technical Notes - National Center for Educational Statistics (DHEW/OE), Washington, DC. Div. of Data Analysis and Dissemination; Stoller, David S.; National Center for Educational Statistics (DHEW/OE), Washington, DC. Div. of Data Analysis and Dissemination ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
This document abstracts 57 Technical Notes of the Division of Data Analysis and Dissemination of the National Center for Educational Statistics which were prepared between May 1966 and April 1968. Among topics discussed are statistical methods, program budgeting, operations analysis, student achievement, cost effectiveness, educational planning, school dropout problems, student teaching, school demography, urban education, occupation studies, and the Educational Opportunities Survey. This document supersedes ED 016 281. (TT)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Abstracts; Academic Achievement; Bibliographies; Cost Effectiveness; Dropout Research; Educational Planning; Educational Quality; Equal Education; Factor Analysis; Models; Operations Research; Program Budgeting; Research Reports; School Demography; Statistical Analysis; Student Teaching; Urban Education; Vocational Education; Coleman Report -- Dynamod II -- ERIC